An inexpensive, charge-balanced rodent deep brain stimulation device: A step-by-step guide to its procurement and construction - Ewing, Samuel G.; Lipski, Witold J.; Grace, Anthony A.; Winter, Christine (Journal of neuroscience methods, 2013)
•The device has an extremely long lifetime with typical stimulation parameters.•The device is initially fully programmable in frequency, pulse-width and current amplitude allowing the study of any common stimulation paradigm.•Two independent outputs are charge-balanced ensuring zero net current delivery per period.•The device is inexpensive and easy to replicate. Despite there being a relatively large number of methods papers which detail specifically the development of stimulation devices, only a small number of reports involve the application of these devices in freely moving animals. To date multiple preclinical neural stimulators have been designed and described but have failed to make an impact on the methods employed by the majority of laboratories studying DBS. Thus, the overwhelming majority of DBS studies are still performed by tethering the subject to an external stimulator. We believe that the low adoption rate of previously described methods is a result of the complexity of replicating and implementing these methods. Here were describe both the design and procurement of a simple and inexpensive stimulator designed to be compatible with commonly used, commercially available electrodes (Plastics 1). This system is initially programmable in frequency, pulsewidth and current amplitude, and delivers biphasic, charge-balanced output to two independent electrodes. It is easy to implement requiring neither subcutaneous implantation nor custom-made electrodes and has been optimized for either direct mounting to the head or for use with rodent jackets. This device is inexpensive and universally accessible, facilitating high throughput, low cost, long-term rodent deep brain stimulation experiments.